PUSH UP MONITORING SYSTEM USING ESP32 FOR REAL-TIME PERFORMANCE ANALYSIS - Rusdiawan, Afif; Alamsyah, Sayyidul Aulia; Peni, Hapsari; Supriyanto, Catur (Universitas Pendidikan Indonesia, 2024)
Health and physical fitness are great concern to society today. One way to maintain health and physical fitness is by exercising. Recently, people seem very enthusiastic about exercising. We can see this from the frequent appearance of videos and photos of people’s sports activities on social media. One of the sports that many people do is push-ups. Many people are familiar with the push-up and often do it to train their arm muscles, or compete in endurance competitions between individuals. Even though they are often done, until now push-ups do not have an integrated monitoring tool so that they can become a credible medium for showing them off on social media. This research aims to create a push-up monitoring tool that can display data in real-time. The push-up monitoring tool is made using an ESP32 microcontroller which is equipped with a VL53L0X distance sensor. By using ESPNOW communication, the special communication between ESP microcontrollers, data can be sent from the push-up monitoring device to a receiver connected to a PC where the monitoring application is displayed. On the PC side, the application is designed to display graphs of distance chest to the ground, average height when the arms are straight, and average height when the arms are bent in real-time. These three aspects are important aspects for observing the validity of a push-up. The results of this research underscore the feasibility of the monitoring system in collecting push-up data. In addition, this research serves as a foundation for future research aimed at simplifying the push up monitoring systems.